2018
DOI: 10.21608/ajs.2018.31668
|View full text |Cite
|
Sign up to set email alerts
|

THE siRNA EFFICACY OF SOLUBLE ACID INVERTASE DOWN-REGULATION IN SUGARCANE (SACCHARUM SPP.)

Abstract: Sugarcane (Saccharum sp. hybrids) is a C4 grass used as a major source of sucrose. Invertase enzymes hydrolyse sucrose into hexose sugars reducing the production markedly. Soluble acid invertase role is always a case of discussion for having a major or minor role in the breakdown process in sink tissues. Bio-deterioration is another serious problem accomplishes the sucrose production, the delay between harvest and milling of sugarcane cause enormous depreciation in cane tonnage as well as sugar recovery. Besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results of Table (3) show that there are significant differences between the fertilizer treatments in the weight of 1000 grains of gm, as the Fe2 treatment gave the highest average of 27.43 g . While the Fe0 treatment gave the lowest mean for this characteristic, reaching 23.87 g. The genotypes differed among themselves, as the Li combination gave the highest average weight of 1000 grains, amounting to 29.45 g, while the gainer combination gave the lowest average, which amounted to 22.34 g. The interaction between cultivars and iron concentrations was significant, as the interaction between the Li composition and the Fe2 treatment gave the highest average for this characteristic, which amounted to 32.39 g, while the interaction between the Rabeh cultivar and the Fe0 fertilizer treatment gave the lowest average, amounting to 20.18 g. The average rate of items…”
Section: Weight Of 1000 Grains (G)mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Table (3) show that there are significant differences between the fertilizer treatments in the weight of 1000 grains of gm, as the Fe2 treatment gave the highest average of 27.43 g . While the Fe0 treatment gave the lowest mean for this characteristic, reaching 23.87 g. The genotypes differed among themselves, as the Li combination gave the highest average weight of 1000 grains, amounting to 29.45 g, while the gainer combination gave the lowest average, which amounted to 22.34 g. The interaction between cultivars and iron concentrations was significant, as the interaction between the Li composition and the Fe2 treatment gave the highest average for this characteristic, which amounted to 32.39 g, while the interaction between the Rabeh cultivar and the Fe0 fertilizer treatment gave the lowest average, amounting to 20.18 g. The average rate of items…”
Section: Weight Of 1000 Grains (G)mentioning
confidence: 99%
“…Because it is involved in many functions such as photosynthesis, formation of chlorophyll, participation in enzymatic reactions, increasing its ability to withstand various stresses and disease resistance, as well as increasing physiological and biochemical activity. The importance of mineral fertilization has been known since 1960 in providing the necessary nutrients to increase the efficiency of agricultural crop production, as it was found that 50% of the increase and improvement in the productivity of grain crops is attributed to the use of mineral fertilizers [3], the lack of micronutrients in Iraqi soils in the different stages of plant growth mother may It is one of the factors affecting the quality of the resulting seeds, so providing these elements, especially iron, through foliar feeding at precise timings coinciding with the growth stages of the plant will avoid exposure to any nutritional stress that wouldlimit the seed yield, as well as addressing the problem of deterioration of seed characteristics as a result for the roles he performs This ingredient increases physiological, chemical and biological activity within plant tissues [4]. Note [5] a study he carried out on the white corn crop in Egypt that an increase in the two concentrations of iron led to an increase in the weight of the grain, as it increased by 10 to 11% for the treatments of iron spraying at a concentration of 100 and 200 mg.l.…”
Section: Introductionmentioning
confidence: 99%